Neurobiobehavioral responses to virtual social rejection in females—exploring the influence of oxytocin. Issue 3 (16th December 2020) - Radke, Sina; Jankowiak, Kathrin; Tops, Sanne; Abel, Ted; Habel, Ute; Derntl, Birgit
Abstract: In recent years, especially adolescents and young adults interact frequently via social media and digital communication. Mimicking an online communication platform where participants could initiate short conversations with two computerized interlocutors, the Verbal Interaction Social Threat Task (VISTTA) was used to induce feelings of social rejection. Motivational and physiological reactions were investigated in 43 healthy young women undergoing functional magnetic resonance imaging (fMRI), of which 22 received 24 international units (IU) intranasal oxytocin and 21 received placebo. Replicating previous findings, social rejection entailed a lower willingness to cooperate with the two peers. Increased activation in the anterior cingulate cortex and bilateral insula/inferior frontal gyrus was observed when receiving negative feedback from others, and in the precuneus when subsequently rating one's willingness to cooperate with them in the future. Oxytocin did not seem to alter responses to social rejection. The current findings provide validation of the VISTTA for examining consequences of rejection in a virtual social interaction that bears a strong resemblance to online communication platforms.